2001
DOI: 10.1016/s0022-5347(05)65973-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Hot Flashes During Treatment With Parenteral Estrogen or Complete Androgen Ablation for Metastatic Carcinoma of the Prostate

Abstract: Endocrine treatment with polyestradiol phosphate induced fewer and less distressing hot flashes than complete androgen ablation. Flashes also disappeared to a greater extent during polyestradiol phosphate than during androgen ablation. The data in this study enable us to provide thorough individual information to patients on the risk and grade of expected distress and duration of hot flashes during polyestradiol phosphate or complete androgen ablation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…A large randomized study in men with M1 prostate cancer, for example, demonstrated that the incidence of hot flashes associated with high-dose parenteral estrogen was 30%, compared with a 74% incidence of hot flashes in men receiving CAB (P<0.001) [18]. Another randomized study in men with M0 prostate cancer found a lower incidence of hot flashes in men receiving bicalutamide monotherapy compared with castration [8].…”
Section: Hot Flashesmentioning
confidence: 99%
“…A large randomized study in men with M1 prostate cancer, for example, demonstrated that the incidence of hot flashes associated with high-dose parenteral estrogen was 30%, compared with a 74% incidence of hot flashes in men receiving CAB (P<0.001) [18]. Another randomized study in men with M0 prostate cancer found a lower incidence of hot flashes in men receiving bicalutamide monotherapy compared with castration [8].…”
Section: Hot Flashesmentioning
confidence: 99%
“…Although most men do not require treatment, a prospective trial found that 11.3% of patients found hot flashes distressing enough to negatively affect their quality of life. 9 Various pharmaceuticals have been used for those men requiring therapy with varying degrees of success. Cyproterone acetate, medroxyprogesterone acetate and clonidine have been reported to be helpful in some patients, although not without the cost of inducing their own side effects.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 One study suggested that the frequency and severity of vasomotor symptoms were most prominent during the first year after castration. 9 In contrary to postmenopausal hot flashes that usually disappear after 2 to 5 years, for men after orchidectomy or receiving continuous GnRH therapy, vasomotor symptoms usually persist. The duration of the symptoms may therefore be quite long, given that many more men are receiving these agents at an earlier stage in their disease.…”
Section: Introductionmentioning
confidence: 99%
“…Spetz et al performed a prospective analysis comparing the incidence of hot flashes in men receiving CAB to that in men receiving estrogen therapy for treatment of PC. 52 In this study, in 915 patients with metastatic disease, 458 were treated with polyestradiol phosphate and 457 patients received CAB. Of men receiving CAB, 74.3% reported hot flashes compared to 30.1% in men receiving estrogen therapy (P , 0.001).…”
Section: Vasomotor Symptoms "Hot Flashes"mentioning
confidence: 99%